2022
DOI: 10.18616/civiltec.v7i1.7212
|View full text |Cite
|
Sign up to set email alerts
|

Índice de Concentração de chuva diária de Timbé do Sul, Santa Catarina

Abstract: A concentração de chuva em alguns períodos pode indicar maior risco de ocorrência de eventos como erosão, inundação e escorregamentos de encostas. O índice de Concentração de chuvas diárias tem sido empregado para avaliar a concentração da precipitação diária e também como indicador da erosividade e agressividade das chuvas. O objetivo deste trabalho foi determinar o Índice de concentração de chuvas para a região de Timbé do Sul, Santa Catarina. Foram utilizados os dados diários de precipitação do período de 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…one can see the variation in CI for the Brazilian territory, with values between 0.50 and 0.65, classified as medium or high risk. These values are in agreement with those obtained byBack et al (2020), who analyzed data from 208 rainfall stations located in the Southern Region of Brazil, and found that CI values ranged from 0.50 to 0.60. AlsoNery et al (2017), analyzing data from 180 stations in the Southeast Region of Brazil, found CI values between 0.54 and 0.60.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…one can see the variation in CI for the Brazilian territory, with values between 0.50 and 0.65, classified as medium or high risk. These values are in agreement with those obtained byBack et al (2020), who analyzed data from 208 rainfall stations located in the Southern Region of Brazil, and found that CI values ranged from 0.50 to 0.60. AlsoNery et al (2017), analyzing data from 180 stations in the Southeast Region of Brazil, found CI values between 0.54 and 0.60.…”
supporting
confidence: 92%
“…In Figure 2 Theoretically, high IC values are located in regions with a high daily concentration of precipitation and, therefore, where precipitation has the potential to generate impacts such as landslides and flood risk (Back et al, 2020;Back et al, 2024).…”
Section: Resultsmentioning
confidence: 99%